Report for proposed new design scheme for Nizam Ambia’s gallery and workshop / Abdul Rahman Abdul Hamid - Abdul Hamid, Abdul Rahman (Faculty of Architecture, Planning and Surveying, 2009)
In these days, there are many films, music, and other artworks by talented individual or independence organization has been produced. But there is still not much people realize about this talented community existing and made them remain in 'underground' industry with their own fund and effort. In addition, they have no chance to present their ability and artworks because of the lack of fullyequipped art centre to support them. This project is to help Nizam Ambia, as the client of this project to obtain its objective to bring these unheard talents to community and make them feel appreciated. The chosen product for this project is PROPOSED NEW DESIGN SCHEME FOR NIZAM AMBIA’S GALLERY AND WORKSHOP. The proposed site which is situated at Lot 131, Seksyen 86 A, Jalan Tun Razak, Kuala Lumpur is well-known-spot among art people since has organize many art events before. The case studies has been done in National Art Gallery, Kuala Lumpur, Islamic Art Musuem and Kuala Lumpur Performing Art Centre in Sentul, Kuala Lumpur, in order to refer the suitable facilities and material application in art centre designing process .The purpose of this project is to equip a place for artist to share his artworks with art lovers. In running this project, the most important of the centre is to upgrade the building into division spaces according to its different function and providing sufficient facilities. It is also to formulate an attraction and instill interest of people on art incessantly. The research methods for this project are based on observation on client’s activities and meeting up them regularly for interview session. The advantages of having this art gallery project, is to experience myself on the activities of independent artist on these days and obtain people’s appreciation towards art especially artwork from names that never been recognized.In view of the fact that the new design of the gallery that will be run should have characters on design, the chosen concept to be applied for the art centre is 'Mysterious Figures of Nature’ as refer to the client’s objective. The design approaches is modern hightech look with using gloomy color such as grey, white and black as the color scheme.